Voices of MA Plus Nurul Islam Sekarbela Students: Perception and Challenges of Artificial Intelligence (AI) in Physics Learning - Ahmad Yadaeni; Dedi Riyan Rizaldi; Rabiatul Hasanah (Mataram University, 2026)
This study aims to determine the extent of perceptions and challenges faced in the application of artificial intelligence (AI) in physics learning. This research activity was conducted at MA Plus Nurul Islam Sekarbela using a mixed method by integrating qualitative and quantitative data. This study sample used a saturated sampling technique with all science students in grades 10, 11, and 12 of MA Plus Nurul Islam Sekarbela. The research data was obtained through three stages: administering a questionnaire, in-depth interviews, and documentation studies. The data obtained were then analyzed descriptively. The results showed that the use of AI in physics learning has provided a positive response from students. This use has become one of the independent learning resources that students can use during class while still paying attention to the limitations set by the teacher. In addition, challenges were found in the implementation process, namely related to the purpose of using AI and the still limited ability of students to evaluate the results of answers or information obtained through AI